Interdisciplinary team working in the Irish primary healthcare system: Analysis of 'invisible' bottom up innovations using Normalisation Process Theory. Issue 11 (November 2019) - Tierney, Edel; Hannigan, Ailish; Kinneen, Libby; May, Carl; O'Sullivan, Madeleine; King, Rachael; Kennedy, Norelee; MacFarlane, Anne
Highlights: Policies encourage interdisciplinary teamwork to improve quality and efficiency of primary care. Interdisciplinary team meetings are often identified as a necessary formal structure for policy implementation. However, informal communication and interactions can also lead to interdisciplinary working that results in organic and 'bottom up' services, yet this has not been empirically analysed. We analyzed the implementation of bottom-up interdisciplinary services in Irish primary care, using Normalisation Process Theory. Findings are discussed in the context of current policy and future policy. Abstract: Interdisciplinary team working in primary care is a key policy goal across healthcare jurisdictions. The National Primary Care Strategy (2001) in Ireland is a top down policy for primary healthcare reform, which prioritised the development and implementation of interdisciplinary Primary Care Teams. The number of Primary Care Teams and features of their clinical meetings have been the key metric in Ireland for appraising progress with the implementation of the strategy. However, these have been challenging to organise in practice. The aim of this paper is to analyse empirical evidence of other forms of interdisciplinary working in Irish primary care, using Normalisation Process Theory. Drawing on data from an on-line survey (71 GPs and 498 other healthcare professionals), and an interview study (37 participants; 8 GPs, 7 practice managers/admin support and 22 health care professionals) in three of the four Health Service Executive (HSE) regions in Ireland, we analyse the nature of these other forms of interdisciplinary working and describe innovations for service delivery that have been developed 'from the ground up' as a result. We examine levers and barriers to the implementation of these bottom up innovations. The levers are that these innovations make sense to professionals, are based on local needs and focus on preventive patient-centred care. They are driven forward by small groups of professionals from different backgrounds with complementary skills. The evaluations show positive impacts of the innovative services for patients, however, many have ceased to operate due to negative effects of the recent economic recession on the Irish healthcare system. These flexible and localised innovations were shaped in part by the reforms set out in the 2001 Primary Care Strategy but also represent unintended effects of that policy because they are the result of bottom up interdisciplinary working that occurs alongside, or instead of, Primary Care Team clinical meetings. Furthermore, as they not captured by existing metrics, the interdisciplinary work and resultant services have been 'invisible' to senior management and policy makers. If appropriately acknowledged and supported, they can shape primary care in the future.